Social Politicies in Times of Crisis - Antón Morón, Antonio (Cuadernos de Trabajo Social, 2012)
The socioeconomic crisis has already lasted four years, its social consequences of massive unemployment, an increase in inequality and new social gaps worsening over time. The need for public protection has widened with the growing risks for social cohesion. The prevailing political management, a liberal-conservative one, prioritizes the interests of the financial markets who are responsible for the crisis. Far from regulating them and pushing forward economic reactivation and job creation, it adopts measures for control and austerity. The consequence is economic stagnation and the prolongation of the crisis, with an attempt to push off its costs again onto the majority of society. Its features are the restriction of the percentage in public social spending per inhabitant in respect to the per capita GDP, a decrease in the strength of protection and an institutional restructuring entailing a bigger segmentation and privatization of public service. At the same time, the majority of the population demands decent employment and guarantees of socioeconomic and labour rights. Social reforms in this period are determined by the dual dynamic, with the option for an exit from the crisis either more regressive or more balanced. The subject of this research is the changes in policies within this context. The social impact of the crisis is analyzed together with the restructuring of the Welfare state, the scare legitimacy of social cuts among the people and the difficulties of and outlook for social reform.
Keywords: Socioeconomic crisis; Inequality; Citizenship; Welfare state; Social reform.